Resident and Staff Satisfaction of Pediatric Graduate Medical Education Training on Transition to Adult Care of Medically Complex Patients. Issue 11 (11th April 2018) - Weeks, Matthew; Cole, Brandon; Flake, Eric; Roy, Daniel
Abstract: Introduction: This study aims to describe the quantity and satisfaction current residents and experienced pediatricians have with graduate medical education on transitioning medically complex patients to adult care. There is an increasing need for transitioning medically complex adolescents to adult care. Over 90% now live into adulthood and require transition to adult healthcare providers. The 2010 National Survey of Children with Special Health Care Needs found that only 40% of youth 12–17 yr receive the necessary services to appropriately transition to adult care. Materials and Methods: Prospective, descriptive, anonymous, web-based survey of pediatric residents and staff pediatricians at Army pediatric residency training programs was sent in March 2017. Questions focused on assessing knowledge of transition of care, satisfaction with transition training, and amount of education on transition received during graduate medical education training. Results: Of the 145 responders (310 potential responders, 47% response rate), transition was deemed important with a score of 4.3 out of 5. The comfort level with transition was rated 2.6/5 with only 4.2% of participants receiving formal education during residency. The most commonly perceived barriers to implementing a curriculum were time constraints and available resources. Of the five knowledge assessment questions, three had a correct response rate of less than 1/3. Conclusions: The findings show the disparity between the presence of and perceived need for a formal curriculum on transitioning complex pediatric patients to adult care. This study also highlighted the knowledge gap of the transition process for novice and experienced pediatricians alike.